(untitled) (Nigerian Journal of Physiological Sciences, 2022)
Hibiscus sabdariffa (HS) has gained attention as an anti-hypertensive agent. In the present study, we hypothesized that anthocyanins from HS may attenuate salt-induced hypertension in rats by suppressing the components of renin-angiotensin-aldoslestrone system (RAAS). Hypertension was induced in the rats by adding 8% NaCl in their diet for six weeks. Wistar rats (n=5 each) were randomly divided into seven groups. Group 1 was the normentensive control group and was fed with normal rat chew and water ad libitum; groups 2 and 3 served as hypertensive control (negative untreated and positive treated with captopril 30mg/kg respectively); groups 4, 5, and 6 served as treatment groups and were administered with graded doses of anthocyanins( 50, 100, 200mg/kg respectively) while group 7 received both 100mg anthocyanins and 30mg captopril per day for 4 weeks. Using HPLC, anthocyanins were isolated from HS calyx following standard protocol. Anthocyanins significantly (p<0.05) reduced blood pressure and heart rate in hypertensive rats in a dose dependent manner. The blood pressure reduction by anthocyanins was associated with a reduction in serum ACE and plasma aldosterone in the hypertensive rats. The effects of anthocyanins on blood pressure and on biomarkers of RAAS were similar to those of captopril, a reference anti-hypertensive drug. The results suggest that anthocyanins exerts a significant (p<0.05) anti-hypertensive potency on rats, probably mediated by the reduction in components of the RAAS. Keywords: hypertension, anthocyanins, renin, aldosterone, rats